Occupation and risk of lymphoid and myeloid leukaemia in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Hosnijeh, Fatemeh Saberi; Christopher, Yvette; Peeters, Petra; Romieu, Isabelle; Xun, Wei; Riboli, Elio; Raaschou-Nielsen, Ole; Tjønneland, Anne; Becker, Nikolaus; Nieters, Alexandra; Trichopoulou, Antonia; Bamia, Christina; et al. (Occupational and environmental medicine, 2013)
Objectives Established risk factors for leukaemia do not explain the majority of leukaemia cases. Previous studies have suggested the importance of occupation and related exposures in leukaemogenesis. We evaluated possible associations between job title and selected hazardous agents and leukaemia in the European Prospective Investigation into Cancer and Nutrition. - Methods The mean follow-up time for 241 465 subjects was 11.20 years (SD 2.42 years). During the follow-up period, 477 incident cases of myeloid and lymphoid leukaemia occurred. Data on 52 occupations considered a priori to be at high risk of developing cancer were collected through standardised questionnaires. Occupational exposures were estimated by linking the reported occupations to a job exposure matrix. Cox proportional hazard models were used to explore the association between occupation and related exposures and risk of leukaemia. - Results The risk of lymphoid leukaemia significantly increased for working in chemical laboratories (HR 8.35, 95% CI 1.58 to 44.24), while the risk of myeloid leukaemia increased for working in the shoe or other leather goods industry (HR 2.54, 95% CI 1.28 to 5.06). Exposure-specific analyses showed a non-significant increased risk of myeloid leukaemias for exposure to benzene (HR 1.15, 95% CI 0.75 to 1.40; HR=1.60, 95% CI 0.95 to 2.69 for the low and high exposure categories, respectively). This association was present both for acute and chronic myeloid leukaemia at high exposure levels. However, numbers were too small to reach statistical significance. - Conclusions Our findings suggest a possible role of occupational exposures in the development of both lymphoid and myeloid leukaemia. Exposure to benzene seemed to be associated with both acute and chronic myeloid leukaemia.
Gesehen am 05.01.2022